A modified electrocatalytic material based on FeTa2O6 and TaON / C and a preparation method thereof
By constructing a heterojunction using FeTa2O6 and TaON/C composite materials, the problem of slow ORR and OER kinetics in zinc-air batteries was solved, achieving efficient and stable bifunctional catalysis suitable for high-stability zinc-air batteries.
Patent Information
- Application Number
- CN202611342827.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-01
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2046-09-01
AI Technical Summary
In existing zinc-air batteries, the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) kinetics are slow, and platinum-based catalysts are costly and have poor stability, making it difficult to achieve efficient bifunctional catalysis.
By employing FeTa2O6 and TaON/C composite materials, a heterojunction is formed through the construction of a three-dimensional conductive network and a hierarchical porous structure. The electron density of active sites is regulated by utilizing the coupling effect of Fe3d/Ta5d/N2p orbitals, thereby optimizing the adsorption energy of oxygen intermediates and enhancing catalytic activity and stability.
It significantly reduces the reaction energy barrier of oxygen reduction and oxygen evolution, improves energy efficiency, inhibits the dissolution and structural degradation of active components, achieves long-term cycle stability and high-efficiency catalytic performance, and is suitable for high-stability zinc-air batteries.
Smart Images

Figure CN122843406B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrocatalytic materials technology, specifically to a modified electrocatalytic material based on FeTa2O6 and TaON / C and its preparation method. Background Technology
[0002] With the rapid development of portable electronic devices, electric vehicles, and large-scale grid energy storage, the demand for electrochemical energy storage systems that combine high energy density, high safety, and low cost is becoming increasingly urgent. Zinc-air batteries, due to their high theoretical energy density (approximately 1086 Wh / kg), abundant zinc resources, and safe, non-toxic, and inexpensive electrolyte, are widely regarded as one of the most promising next-generation energy storage technologies. In zinc-air batteries, the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) at the air cathode are the core processes determining battery performance; however, both reactions generally suffer from slow kinetics, severely limiting the battery's power density and cycle life. Platinum-based catalysts, due to their excellent ORR catalytic activity (especially high half-wave potential and high electron transport efficiency), have become a research hotspot for zinc-air battery cathode materials. However, platinum-based catalysts also face multiple challenges in practical applications: the scarcity and high price of platinum resources lead to high battery costs; during long-term cycling, platinum nanoparticles are prone to aggregation, migration, or carbon support corrosion, resulting in poor stability and decreased catalytic activity; in addition, platinum has relatively limited catalytic activity for OER, making it difficult to achieve efficient bifunctional catalysis.
[0003] To address the aforementioned issues, researchers have attempted to reduce costs while enhancing catalytic stability and bifunctional activity by introducing oxide or oxynitride supports. Among these, tantalum oxynitride (TaON) has attracted widespread attention due to its unique electronic structure and chemical stability. Studies have shown that the heterostructure formed by TaON and carbon materials can effectively regulate interfacial electron density, improve charge transfer efficiency, and enhance the adsorption and activation of oxygen intermediates. However, there is still room for improvement in the bifunctional catalytic activity of single TaON-based supports. Iron tantalate (FeTa2O6), as a tantalum-based bimetallic oxide with a trirutile structure, shows promising application potential in electrocatalysis. FeTa2O6 possesses excellent chemical stability and abundant surface active sites, and its combination with carbon materials exhibits superior electrocatalytic activity and stability. Summary of the Invention
[0004] In view of the shortcomings of the prior art, the purpose of this invention is to provide a modified electrocatalytic material based on FeTa2O6 and TaON / C and its preparation method.
[0005] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing a modified electrocatalytic material based on FeTa2O6 and TaON / C includes the following preparation steps: S1. Mix FeCl3·6H2O and TaCl5 powder in a 1:1 mass ratio, slowly add alcohol while grinding, and grind until there are no obvious particles to obtain a mixed powder; S2. Place the mixed powder in a forced-air drying oven to dry, calcine at 780-820℃ for 2-3 hours under an argon atmosphere, and wash and dry after natural cooling to obtain FeTa2O6; S3. By mass, mix and grind 2-3 parts FeTa2O6 with 8-12 parts g-C3N4, 8-12 parts FeCl3·6H2O, 1-1.2 parts element modifier and 8-12 parts structure modifier until there are no obvious particles. While grinding, slowly add 0.15-0.25 parts alcohol. S4. Place the powder ground in step S3 in a forced-air drying oven to dry, calcine at 780-820℃ for 2-3 hours under an argon atmosphere, and wash and dry after natural cooling to obtain the modified electrocatalytic material; The preparation of the structural modifier includes the following steps: S11. By weight, add 11-12 parts sodium alginate, 0.2-0.5 parts carbon nanotubes, and 0.3-0.8 parts graphene oxide to 80-100 parts deionized water and ultrasonically disperse at a frequency of 40kHz for 1-2 hours. S12. Add 0.5-1 part of urea to the dispersion obtained in step S11, stir evenly, and then slowly drop the mixture into 180-200 parts of calcium chloride solution with a mass concentration of 5%. After the addition is complete, let it stand for cross-linking for 10-12 hours, take it out and wash it with deionized water 3-4 times, and dry it at 58-60℃ for 20-24 hours. S13. Place the gel obtained in step S12 in a tube furnace and carbonize it at 600-700℃ for 2-3 hours under an argon atmosphere. After immersion in dilute hydrochloric acid for 6-12 hours, wash it with water until neutral. Finally, dry and grind it to obtain the structure modifier powder.
[0006] Preferably, the preparation of the element modifier includes the following steps: S21. By weight, mix 0.5-1 parts of auxiliary modifier with 50-80 parts of deionized water, stir at 400-500 r / min until completely dissolved, then add 0.2-0.5 parts of 50% manganese nitrate solution and continue stirring for 8-10 min. S22. Add 1-2 parts of citric acid to the mixture obtained in step S21, continue stirring until completely dissolved, then place it in an 80-90℃ water bath and stir to evaporate to a viscous sol. Transfer it to a forced-air drying oven and dry at 110-120℃ for 12-24 hours. S23. Grind the dry gel obtained in step S22 evenly, calcine it in a tube furnace at 450-550℃ for 2-3 hours under an argon atmosphere, with a heating rate of 2-3℃ / min, and grind it after naturally cooling to room temperature to finally obtain the element modifier.
[0007] Preferably, the preparation of the auxiliary modifier includes the following steps: S211. By mass, mix 0.5-1 parts Co(NO3)2·6H2O, 0.5-1 parts Ni(NO3)2·6H2O, 0.2-0.5 parts ammonium molybdate with 30-50 parts deionized water, and stir at 400-500 r / min for 20-30 min. S212. Add 0.2-0.5 parts of PVP-K30 and 2-3 parts of citric acid to the mixture obtained in step S211, continue stirring for 30-40 minutes, then heat and evaporate in a 75-85℃ water bath until it becomes a sol, transfer it to a forced-air drying oven, and dry at 110-120℃ for 12-24 hours. S213. Grind the dry gel obtained in step S212 evenly, calcine it in a tube furnace at 450-550℃ for 2-3 hours under an argon atmosphere, with a heating rate of 2-3℃ / min, and grind it after it cools naturally to room temperature to finally obtain the auxiliary modifier.
[0008] Preferably, the mass ratio of alcohol to TaCl5 powder in step S1 is 0.05-0.1:1.
[0009] Preferably, the calcination heating rate in steps S2 and S4 is 4-5℃ / min.
[0010] Preferably, the washing in steps S2 and S4 involves alternating washing with ethanol and deionized water until the solution is neutral.
[0011] Preferably, the heating rate of the carbonization process in step S13 is 2-3℃ / min.
[0012] Preferably, the concentration of dilute hydrochloric acid in step S13 is 1-2 mol / L.
[0013] Preferably, the stirring speed in step S211 is 400-500 r / min.
[0014] A modified electrocatalytic material based on FeTa2O6 and TaON / C was prepared by the above-described method.
[0015] Compared with the prior art, the beneficial effects of the present invention are: 1. The structural modifier of this invention constructs a three-dimensional conductive network and a hierarchical porous structure, achieving efficient exposure of active sites and mass transport. The auxiliary modifier and elemental modifier synergistically construct a multi-element metal oxide heterojunction, significantly enhancing bifunctional catalytic activity.
[0016] 2. This invention introduces FeTa2O6 to form a heterojunction with TaON / C. Utilizing the strong coupling effect of Fe3d / Ta5d / N2p orbitals at the heterojunction interface, and in conjunction with structural and elemental modifiers, it regulates the electron density of active sites, optimizes the adsorption energy of oxygen intermediates, and significantly reduces the reaction energy barrier for oxygen reduction and oxygen evolution. This effectively reduces battery polarization during charge and discharge, and improves energy efficiency. Simultaneously, the inorganic oxide and nitrogen oxide framework of the heterostructure endows the catalyst with excellent corrosion resistance, effectively inhibiting the dissolution and structural degradation of active components during long-term charge and discharge, stabilizing catalytic active sites, and maintaining continuous and efficient catalytic performance.
[0017] 3. The modified electrocatalytic material of this invention exhibits excellent long-term cycle stability and rate performance in zinc-air batteries, and is suitable for zinc-air battery systems with high stability and long lifespan. Attached Figure Description
[0018] Figure 1 This is a flowchart of the preparation process of the present invention; Figure 2 The images shown are SEM images of the modified electrocatalytic material obtained in Example 1 of this invention, where a is the SEM image at 1 μm and b is the SEM image at 500 nm. Figure 3 The image shows the HRTEM image of the modified electrocatalytic material obtained in Example 1 of this invention. Figure 4 The image shows a linear sweep voltammetry comparison of the ORR (redox reaction) of the modified electrocatalytic materials obtained in Example 2 and Comparative Example 1 before and after 5000 cycles. Figure 5 The image shows a linear sweep voltammetry comparison of the modified electrocatalytic materials obtained in Example 2 and Comparative Example 1 before and after 5000 cycles of the OER (oxygen evolution reaction). Figure 6 This is a comparison chart of the power density and polarization curves of the modified electrocatalytic materials obtained in Example 2 and Comparative Example 1 of the present invention. Detailed Implementation
[0019] The present invention will now be clearly and completely described in conjunction with embodiments thereof. Obviously, the described embodiments are merely some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0020] Please see Figures 1-6 The present invention provides a technical solution: Example 1 A method for preparing modified electrocatalytic materials based on FeTa2O6 and TaON / C: Before preparing the modified electrocatalytic material, auxiliary modifiers, structural modifiers, and elemental modifiers are prepared first: The preparation of the auxiliary modifier includes the following steps: S211. Mix 0.5g Co(NO3)2·6H2O, 0.5g Ni(NO3)2·6H2O, 0.2g ammonium molybdate with 30g deionized water and stir at 400r / min for 20min; S212. Add 0.2g PVP-K30 and 2g citric acid to the mixture obtained in step S211, continue stirring for 30min, then heat in a 75℃ water bath to evaporate to a sol state, transfer to a forced-air drying oven, and dry at 110℃ for 12h. S213. Grind the dry gel obtained in step S212 evenly, calcine it in a tube furnace at 450°C for 2 hours under an argon atmosphere with a heating rate of 2°C / min, and grind it after naturally cooling to room temperature to finally obtain the auxiliary modifier.
[0021] The preparation of the structural modifier includes the following steps: S11. Add 11g sodium alginate, 0.2g carbon nanotubes and 0.3g graphene oxide to 80g deionized water and disperse ultrasonically at 40kHz for 1h. S12. Add 0.5g of urea to the dispersion obtained in step S11, stir evenly, and then slowly drop the mixture into 180g of calcium chloride solution with a mass concentration of 5%. After the addition is complete, let it stand for cross-linking for 10h, take it out, wash it with deionized water 3 times, and dry it at 58℃ for 20h. S13. The gel obtained in step S12 is placed in a tube furnace and carbonized at 600°C for 2 hours under an argon atmosphere (heating rate 2°C / min). After being acid-soaked in 1 mol / L dilute hydrochloric acid for 6 hours, it is washed with water until neutral. After drying and grinding, the structure modifier powder is finally obtained.
[0022] The preparation of element modifiers includes the following steps: S21. Mix 0.5g of auxiliary modifier with 50g of deionized water, stir at 400r / min until completely dissolved, then add 0.2g of 50% manganese nitrate solution and continue stirring for 8min; S22. Add 1g of citric acid to the mixture obtained in step S21, continue stirring until completely dissolved, then place it in an 80℃ water bath and stir to evaporate to a viscous sol. Transfer it to a forced-air drying oven and dry at 110℃ for 12h. S23. Grind the dry gel obtained in step S22 evenly, calcine it in a tube furnace at 450°C for 2 hours under an argon atmosphere with a heating rate of 2°C / min, and grind it after naturally cooling to room temperature to finally obtain the element modifier.
[0023] The preparation of modified electrocatalytic materials includes the following steps: S1. Mix FeCl3·6H2O and TaCl5 powder in a mass ratio of 1:1, and slowly add alcohol (the mass ratio of alcohol to TaCl5 powder is 0.05:1) while grinding, and grind until there are no obvious particles to obtain a mixed powder; S2. The mixed powder was placed in a forced-air drying oven and dried. It was then calcined at 780℃ (heating rate of 4℃ / min) for 2 hours under an argon atmosphere. After natural cooling, it was washed (alternating between ethanol and deionized water until neutral) and dried to obtain FeTa2O6. S3. Mix and grind 2g FeTa2O6 with 8g G-C3N4, 8g FeCl3·6H2O, 1g element modifier and 8g structure modifier until there are no obvious particles. While grinding, slowly add 0.15g alcohol. S4. Place the powder ground in step S3 in a forced-air drying oven to dry, calcine at 780℃ (heating rate of 4℃ / min) for 2 hours under an argon atmosphere, and wash (using alternating washing with ethanol and deionized water until neutral) after natural cooling and drying to obtain the modified electrocatalytic material.
[0024] Example 2 A method for preparing modified electrocatalytic materials based on FeTa2O6 and TaON / C: Before preparing the modified electrocatalytic material, auxiliary modifiers, structural modifiers, and elemental modifiers are prepared first: The preparation of the auxiliary modifier includes the following steps: S211. Mix 1g Co(NO3)2·6H2O, 1g Ni(NO3)2·6H2O, 0.5g ammonium molybdate with 50g deionized water and stir at 500r / min for 30min. S212. Add 0.5g PVP-K30 and 3g citric acid to the mixture obtained in step S211, continue stirring for 40min, then heat in an 85℃ water bath to evaporate to a sol state, transfer to a forced-air drying oven, and dry at 120℃ for 24h. S213. Grind the dry gel obtained in step S212 evenly, calcine it in a tube furnace at 550°C for 3 hours under an argon atmosphere with a heating rate of 3°C / min, and grind it after naturally cooling to room temperature to finally obtain the auxiliary modifier.
[0025] The preparation of the structural modifier includes the following steps: S11. Add 12g sodium alginate, 0.5g carbon nanotubes and 0.8g graphene oxide to 100g deionized water and disperse ultrasonically at 40kHz for 2h. S12. Add 1g of urea to the dispersion obtained in step S11, stir evenly, and then slowly drop the mixture into 200g of calcium chloride solution with a mass concentration of 5%. After the addition is complete, let it stand for cross-linking for 12h, take it out, wash it 4 times with deionized water, and dry it at 60℃ for 24h. S13. The gel obtained in step S12 is placed in a tube furnace and carbonized at 700°C for 3 hours under an argon atmosphere (heating rate 3°C / min). After being acid-soaked in 2 mol / L dilute hydrochloric acid for 12 hours, it is washed with water until neutral. After drying and grinding, the structure modifier powder is finally obtained.
[0026] The preparation of element modifiers includes the following steps: S21. Mix 1g of auxiliary modifier with 80g of deionized water, stir at 500r / min until completely dissolved, then add 0.5g of 50% manganese nitrate solution and continue stirring for 10min. S22. Add 2g of citric acid to the mixture obtained in step S21, continue stirring until completely dissolved, then place it in a 90℃ water bath and stir to evaporate to a viscous sol. Transfer it to a forced-air drying oven and dry at 120℃ for 24h. S23. Grind the dry gel obtained in step S22 evenly, calcine it in a tube furnace at 550°C for 3 hours under an argon atmosphere with a heating rate of 3°C / min, and grind it after naturally cooling to room temperature to finally obtain the element modifier.
[0027] The preparation of modified electrocatalytic materials includes the following steps: S1. Mix FeCl3·6H2O and TaCl5 powder in a mass ratio of 1:1, and slowly add alcohol (the mass ratio of alcohol to TaCl5 powder is 0.1:1) while grinding, and grind until there are no obvious particles to obtain a mixed powder; S2. The mixed powder was placed in a forced-air drying oven and dried. It was then calcined at 820℃ (heating rate of 5℃ / min) for 3 hours under an argon atmosphere. After natural cooling, it was washed (alternating between ethanol and deionized water until neutral) and dried to obtain FeTa2O6. S3. Mix 3g FeTa2O6 with 12g G-C3N4, 12g FeCl3·6H2O, 1.2g element modifier and 12g structure modifier and grind until there are no obvious particles. While grinding, slowly add 0.25g alcohol. S4. Place the powder ground in step S3 in a forced-air drying oven to dry, calcine at 820℃ (heating rate of 5℃ / min) for 3 hours under an argon atmosphere, and wash (using alternating washing with ethanol and deionized water until neutral) after natural cooling and drying to obtain the modified electrocatalytic material.
[0028] Example 3 A method for preparing modified electrocatalytic materials based on FeTa2O6 and TaON / C: Before preparing the modified electrocatalytic material, auxiliary modifiers, structural modifiers, and elemental modifiers are prepared first: The preparation of the auxiliary modifier includes the following steps: S211. Mix 0.7g Co(NO3)2·6H2O, 0.7g Ni(NO3)2·6H2O, 0.3g ammonium molybdate with 40g deionized water and stir at 450r / min for 25min. S212. Add 0.3g PVP-K30 and 2.2g citric acid to the mixture obtained in step S211, continue stirring for 35min, then heat in an 80℃ water bath to evaporate to a sol state, transfer to a forced-air drying oven, and dry at 115℃ for 18h. S213. Grind the dry gel obtained in step S212 evenly, calcine it in a tube furnace at 500℃ for 2.5h under an argon atmosphere with a heating rate of 2.5℃ / min, and grind it after it cools naturally to room temperature to finally obtain the auxiliary modifier.
[0029] The preparation of the structural modifier includes the following steps: S11. Add 11.5g sodium alginate, 0.3g carbon nanotubes, and 0.5g graphene oxide to 90g deionized water and ultrasonically disperse at a frequency of 40kHz for 1.5h. S12. Add 0.7g of urea to the dispersion obtained in step S11, stir evenly, and then slowly drop the mixture into 190g of calcium chloride solution with a mass concentration of 5%. After the addition is complete, let it stand for cross-linking for 11h, take it out, wash it 3 times with deionized water, and dry it at 59℃ for 22h. S13. The gel obtained in step S12 is placed in a tube furnace and carbonized at 650°C for 2.5 h under an argon atmosphere (heating rate 2.5°C / min). After acid immersion in 1.5 mol / L dilute hydrochloric acid for 8 h, it is washed with water until neutral. After drying and grinding, the structure modifier powder is finally obtained.
[0030] The preparation of element modifiers includes the following steps: S21. Mix 0.7g of auxiliary modifier with 60g of deionized water, stir at 450r / min until completely dissolved, then add 0.3g of 50% manganese nitrate solution and continue stirring for 9min; S22. Add 1.5g of citric acid to the mixture obtained in step S21, continue stirring until completely dissolved, then place in an 85℃ water bath and stir to evaporate to a viscous sol, transfer to a forced-air drying oven and dry at 115℃ for 18h; S23. Grind the dry gel obtained in step S22 evenly, calcine it in a tube furnace at 500℃ for 2.5h under argon atmosphere with a heating rate of 2.5℃ / min, and grind it after natural cooling to room temperature to finally obtain the element modifier.
[0031] The preparation of modified electrocatalytic materials includes the following steps: S1. Mix FeCl3·6H2O and TaCl5 powder in a mass ratio of 1:1, and slowly add alcohol (the mass ratio of alcohol to TaCl5 powder is 0.07:1) while grinding, and grind until there are no obvious particles to obtain a mixed powder; S2. The mixed powder was placed in a forced-air drying oven and dried. It was then calcined at 800℃ (heating rate of 4.5℃ / min) for 2.5h under an argon atmosphere. After natural cooling, it was washed (alternating between ethanol and deionized water until neutral) and dried to obtain FeTa2O6. S3. Mix 2.5g FeTa2O6 with 10g G-C3N4, 10g FeCl3·6H2O, 1.1g element modifier and 10g structure modifier and grind until there are no obvious particles. While grinding, slowly add 0.2g alcohol. S4. The powder ground in step S3 is placed in a forced-air drying oven for drying, calcined at 800℃ (heating rate of 4.5℃ / min) for 2.5h under an argon atmosphere, and then washed (using alternating washing with ethanol and deionized water until neutral) and dried to obtain the modified electrocatalytic material.
[0032] Comparative Example 1 The only difference between Comparative Example 1 and Example 1 is that no elemental modifier was added in this comparative example; the remaining steps are exactly the same in both Comparative Example 1 and Example 1.
[0033] Comparative Example 2 The only difference between Comparative Example 2 and Example 1 is that no structural modifier was added in this comparative example; the other steps are exactly the same in Comparative Example 2 and Example 1.
[0034] Performance testing: Take 5 mg of the modified electrocatalytic material obtained in Examples 1-3 and Comparative Examples 1-2 respectively, mix it with 10 μL of Nafion solution and 100 μL of ethanol solution, and stir vigorously for 24 h to obtain a uniform and fine black slurry.
[0035] The slurry was coated onto a disk electrode or a platinum-carbon electrode as the working electrode, an Ag / AgCl electrode as the reference electrode, and a platinum mesh electrode as the counter electrode. ORR and OER performance were tested using this three-electrode system (test results are attached). Figure 4-5 ).
[0036] The slurry was coated onto carbon paper and dried at room temperature. The dried carbon paper served as the positive electrode, and the zinc sheet as the negative electrode. The battery was assembled in air in the order of battery casing, carbon paper, and zinc sheet. 6M potassium hydroxide was then added as the electrolyte. After assembly, electrochemical performance tests were performed. The test results are shown in Table 1 below. Table 1 Performance Test Results As shown in Table 1, the modified electrocatalytic materials obtained in Examples 1-3 outperform the comparative examples in all aspects of performance. This further illustrates that the present invention, by introducing FeTa2O6 to form a heterojunction with TaON / C, utilizes the strong coupling effect of Fe3d / Ta5d / N2p orbitals at the heterojunction interface, in conjunction with structural and elemental modifiers, to effectively improve energy efficiency, stabilize catalytic active sites, and maintain consistently high catalytic performance.
[0037] Appendix Figure 2 The images show SEM images of the modified electrocatalytic material obtained in Example 1 of this invention, where a is the SEM image at 1 μm and b is the SEM image at 500 nm. Figure 3 This is an HRTEM image of the modified electrocatalytic material obtained in Example 1 of the present invention. (From the attached image) Figure 2 and attached Figure 3 As can be seen, the high-resolution transmission electron microscope image clearly shows two different lattice fringes: the (002) crystal plane (d=0.256 nm) belonging to TaON and the (110) crystal plane (d=0.322 nm) belonging to FeTa2O6. The structure is distinct at the nanoscale interface, which confirms that the heterojunction structure has been successfully constructed and the modified electrocatalytic material has been successfully prepared.
[0038] Appendix Figure 4 This is a comparison of the ORR (Organic Rate) before and after 5000 cycles for the modified electrocatalyst materials obtained in Example 2 and Comparative Example 1 of this invention. (See attached image.) Figure 5 This is a linear sweep voltammetry comparison of the modified electrocatalytic materials obtained in Example 2 and Comparative Example 1 before and after 5000 OER cycles. (See attached image.) Figure 4 (ORR) and appendix Figure 5(OER) results show that the modified electrocatalytic material maintained a half-wave potential of 0.831V after 5000 CV cycles. The half-wave potential of Example 2 decreased by only 23mV, while the overpotential increased by 11mV. In contrast, the half-wave potential and overpotential of Comparative Example 1 decreased by 73mV and 58mV, respectively, both showing a decline. Based on these test results, the stability of the modified electrocatalytic material prepared in Example 2 is significantly improved.
[0039] Appendix Figure 6 This is a comparison of the power density and polarization curves of the modified electrocatalytic materials obtained in Example 2 and Comparative Example 1 of the present invention. As can be seen from the figure, the power density of Example 2 is superior to that of Comparative Example 1 at all different current densities. The voltage drop of the polarization curve of Example 2 with increasing current density is less significant than that of Comparative Example 1, indicating that its polarization resistance is lower. With increasing current density, the power density of Example 2 decreases more gradually, and the maximum power density reaches 208.3 mW / cm². -2 It is higher than the 109.9 mW cm of Comparative Example 1. -2 This indicates that the FeTa2O6-TaON / C heterostructure effectively improves the power output capability and rate performance of the battery.
[0040] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A preparation method of a modified electrocatalytic material based on FeTa20 6 and TaON / C, characterized in that, The preparation steps include the following: S1. Mix FeCl3·6H2O and TaCl5 powder in a 1:1 mass ratio, slowly add alcohol while grinding, and grind until there are no obvious particles to obtain a mixed powder; S2. Place the mixed powder in a forced-air drying oven to dry, calcine at 780-820℃ for 2-3 hours under an argon atmosphere, and wash and dry after natural cooling to obtain FeTa2O6; S3. By mass, mix and grind 2-3 parts FeTa2O6 with 8-12 parts g-C3N4, 8-12 parts FeCl3·6H2O, 1-1.2 parts element modifier and 8-12 parts structure modifier until there are no obvious particles. While grinding, slowly add 0.15-0.25 parts alcohol. S4. The powder ground in step S3 is placed in a forced-air drying oven for drying, calcined at 780-820℃ for 2-3 hours under an argon atmosphere, and then washed and dried after natural cooling to obtain the modified electrocatalytic material, in which FeTa2O6 forms a heterojunction with TaON / C. The preparation of the structural modifier includes the following steps: S11. By weight, add 11-12 parts sodium alginate, 0.2-0.5 parts carbon nanotubes, and 0.3-0.8 parts graphene oxide to 80-100 parts deionized water and ultrasonically disperse at a frequency of 40kHz for 1-2 hours. S12. Add 0.5-1 part of urea to the dispersion obtained in step S11, stir evenly, and then slowly drop the mixture into 180-200 parts of calcium chloride solution with a mass concentration of 5%. After the addition is complete, let it stand for cross-linking for 10-12 hours, take it out and wash it with deionized water 3-4 times, and dry it at 58-60℃ for 20-24 hours. S13. Place the gel obtained in step S12 in a tube furnace and carbonize it at 600-700℃ for 2-3 hours under an argon atmosphere. After immersion in dilute hydrochloric acid for 6-12 hours, wash it with water until neutral. Finally, dry and grind it to obtain the structure modifier powder. The preparation of the element modifier includes the following steps: S21. By weight, mix 0.5-1 parts of auxiliary modifier with 50-80 parts of deionized water, stir at 400-500 r / min until evenly dispersed, then add 0.2-0.5 parts of 50% manganese nitrate solution and continue stirring for 8-10 min. S22. Add 1-2 parts of citric acid to the mixture obtained in step S21, continue stirring until completely dissolved, then place it in an 80-90℃ water bath and stir to evaporate to a viscous sol. Transfer it to a forced-air drying oven and dry at 110-120℃ for 12-24 hours. S23. Grind the dry gel obtained in step S22 evenly, calcine it in a tube furnace at 450-550℃ for 2-3 hours under an argon atmosphere, with a heating rate of 2-3℃ / min, and grind it after naturally cooling to room temperature to finally obtain the element modifier. The preparation of the auxiliary modifier includes the following steps: S211. By mass, mix 0.5-1 parts Co(NO3)2·6H2O, 0.5-1 parts Ni(NO3)2·6H2O, 0.2-0.5 parts ammonium molybdate with 30-50 parts deionized water and stir for 20-30 minutes; S212. Add 0.2-0.5 parts of PVP-K30 and 2-3 parts of citric acid to the mixture obtained in step S211, continue stirring for 30-40 minutes, then heat and evaporate to a sol state in a water bath at 75-85℃, transfer to a forced-air drying oven, and dry at 110-120℃ for 12-24 hours. S213. Grind the dry gel obtained in step S212 evenly, calcine it in a tube furnace at 450-550℃ for 2-3 hours under an argon atmosphere, with a heating rate of 2-3℃ / min, and grind it after it cools naturally to room temperature to finally obtain the auxiliary modifier.
2. The method for preparing a modified electrocatalytic material based on FeTa2O6 and TaON / C according to claim 1, characterized in that, In step S1, the mass ratio of alcohol to TaCl5 powder is 0.05-0.1:
1.
3. The method for preparing a modified electrocatalytic material based on FeTa2O6 and TaON / C according to claim 1, characterized in that, The calcination heating rate in steps S2 and S4 is 4-5℃ / min.
4. The method for preparing a modified electrocatalytic material based on FeTa2O6 and TaON / C according to claim 1, characterized in that, The washing in steps S2 and S4 involves alternating washing with ethanol and deionized water until the solution is neutral.
5. The method for preparing a modified electrocatalytic material based on FeTa2O6 and TaON / C according to claim 1, characterized in that, The heating rate of the carbonization process in step S13 is 2-3℃ / min.
6. The method for preparing a modified electrocatalytic material based on FeTa2O6 and TaON / C according to claim 1, characterized in that, In step S13, the concentration of dilute hydrochloric acid is 1-2 mol / L.
7. The method for preparing a modified electrocatalytic material based on FeTa2O6 and TaON / C according to claim 1, characterized in that, The stirring speed in step S211 is 400-500 r / min.
8. A modified electrocatalytic material based on FeTa2O6 and TaON / C, characterized in that, It is prepared by the preparation method described in any one of claims 1-7.
Citation Information
Patent Citations
Precious metal, active metal and modified support - containing hydrogenation catalysts and acetic acid hydrogenation process using the same
CN104039446A
Preparation method for Ni-Co / carbon nanotube aerogel catalyst of zinc-air battery
CN105609790A
